PENGARUH JOB STRESS DAN WORK-LIFE BALANCE TERHADAP JOB PERFORMANCE PEGAWAI DIREKTORAT JENDERAL PAJAK YANG DIMEDIASI JOB SATISFACTION - Nasikhudin, Nasikhudin; Muttaqijn, Imam; Gumilar, Aris (JURNAL PAJAK INDONESIA, 2024)
This study seeks to examine the influence of workplace stress as well as work-life balance on employees' performance at the Directorate General of Taxes (DGT) through the mediation of job satisfaction. This research aims to investigate the effect of implementing remote work at DGT during the COVID-19 epidemic, specifically focusing on the potential effects of increased stress, work-life imbalance, as well as decreased employee performance. This study employed a quantitative approach, involving 504 employees of DGT, who were selected as respondents from diverse backgrounds in terms of age, education, marital status, length of service, as well as position. The respondents were located across several regions of Indonesia. Multiple linear regression as well as path analysis are employed for analysis, along with statistical testing utilizing the t-test as well as F-test. The results of the hypothesis test indicated a significant as well as unfavorable effect of job stress on both job satisfaction as well as performance. The equilibrium among work as well as personal life has a notable as well as beneficial influence on both job contentment as well as productivity. Job satisfaction could serve as a mediator in the connection among job stress as well as work-life balance, influencing the job performance of DGT personnel.